The first megatheropod tracks from the Lower Jurassic upper Elliot Formation, Karoo Basin, Lesotho. - L Sciscio (PLoS ONE, 2017)
A palaeosurface with one megatheropod trackway and several theropod tracks and trackways from the Lower Jurassic upper Elliot Formation (Stormberg Group, Karoo Supergroup) in western Lesotho is described. The majority of the theropod tracks are referable to either Eubrontes or Kayentapus based on their morphological characteristics. The larger megatheropod tracks are 57 cm long and have no Southern Hemisphere equivalent. Morphologically, they are more similar to the Early Jurassic Kayentapus, as well as the much younger Upper Cretaceous ichnogenus Irenesauripus, than to other contemporaneous ichnogenera in southern Africa. Herein they have been placed within the ichnogenus Kayentapus and described as a new ichnospecies (Kayentapus ambrokholohali). The tracks are preserved on ripple marked, very fine-grained sandstone of the Lower Jurassic upper Elliot Formation, and thus were made after the end-Triassic mass extinction event (ETE). This new megatheropod trackway site marks the first occurrence of very large carnivorous dinosaurs (estimated body length >8-9 meters) in the Early Jurassic of southern Gondwana, an evolutionary strategy that was repeatedly pursued and amplified in the following ~135 million years, until the next major biotic crisis at the end-Cretaceous.